Operating Permissioned Blockchain in Clouds: A Performance Study of Hyperledger Sawtooth - Shi, Zeshun; Zhou, Huan; Hu, Yang; Jayachander, Surbiryala; de Laat, Cees; Zhao, Zhiming (2019 18th International Symposium on Parallel and Distributed Computing (ISPDC), 2019)
With ever more IoT (Internet of Things) and bigdata applications, the emerging blockchain techniques provide fundamental supports to credibly track the transactions of digital assets. Public blockchains, e.g., bitcoin, are often energy-consuming and low efficient. Therefore, an empirical study of operating permissioned blockchains in clouds is urgently needed. In this paper, we study the performance of Sawtooth, a well-known permissioned blockchain platforms from Hyperledger, in cloud environments. Our results provide insights for blockchain operators to optimize the performance of Sawtooth through adjusting the two configuration parameters, i.e., Scheduler and Maximum Batches Per Block. Our approach can be used to test other blockchain platforms.